Shorthaired cats in America - Quasha, Jennifer (New York : PowerKids Press, 2000)
Discusses the history of non-pedigreed shorthaired cats in America.
Includes index.
Keywords: American shorthair cat -- Juvenile literature; American shorthair cat; Cats